O ensino de língua inglesa nos 6° e 7° anos do ensino fundamental da unidade de ensino básico jornalista Neiva Moreira: o material didático em foco - COSTA, Luiz Máximo Lima (2023)
This study is about the teaching of English, specifically, in the 6th and 7th years of elementary school, in the Unidade de Ensino Básico Jornalista Neiva Moreira school, which also brings to discussion the process of choosing the teaching material, in particular, the textbook . The option for this theme was due to the perception of some vulnerabilities, among them, the finding of ineffective teaching and the lack of resources and teaching materials according to the reality of the students, although the curricular component English Language is legally required in the curriculum school, since the 6th year of elementary school. Therefore, a guiding question outlined this research that is if the didactic material, in particular, the textbook of the 6th and 7th years of the investigated educational institution, is or not decisive for success of English teaching process. To a better understanding of this question, the main objective of this work was to analyze the process of choosing teaching materials, with emphasis on the book used in the 6th and 7th years of the previoulsy mentioned school, with the aim of developing its potential in current teaching conditions. In relation to methodology, a bibliographical survey was initially organized, based on the bibliography of Leffa (1999, 2006, 2008, 2016), Martinez (2009), Moita Lopes (1996, 2009, 2013), Cavalcante (2011), Almeida Filho (2013), Paes and Jorge (2013), Souza (2011), Lopes and Macedo (2011) Goodson (2018), and many others. After that, it is applied a field research, in which the data collection tool was a semi-structured interview with three of their English teachers. It was also analyzed, in methodology, the books of the 6th and 7th years of English Language, used in the investigated teaching unit. The results showed that the didactic material, in particular, the textbook for the 6th and 7th grades, is fundamental for success in the English teaching process. Other concepts of langue and language inserted in this didactic material predominantly permeate the communicative approach, which recommends the teaching of a foreign language in a way that is closer to the reality of the users of the language. It was also noticed a relationship with the curricular guidelines, especially with the Base Nacional Comum Curricular (BNCC), which aims at teaching based on plurality and diversity.